Property Rights and Social Justice - Kowalik, Tadeusz (Studia Historiae Oeconomicae, 2011)
There is already a rich literature on property transformations in Poland. However, in this literature, works considering them from the point of view of respecting principles of social justice if we leave out of consideration the calming statement that privatisation by its very nature could not be fair. These are rarely considered from the point of view that would seem obvious — of observing the principles of social justice. An exception here would be the appeasing statement, frequently expressed especially during the first years of transformation, that privatisation by its very nature could not have been fair. Indeed, perhaps it could not have been fully fair. But did it have to be so blatantly unfair? Taking up this theme, it is worth departing from a bipolar view (just or unjust) in favour of the concept of graded justice. Let’s try to look at some of the most promising (even programmatic) threads of privatisation in Poland (even if only provided by the programme) through the prism of the principles of social justice which are after all part of the Constitution. Analysing the problem of the relation between ownership transformation and the idea of social justice, the author examines in turn: ignoring of the idea of "democratic ownership" by the economic and political elites which had a direct impact on the processes of privatisation, the problem of employee-owned companies, the idea of mass privatisation programme implemented in the National Investment Fund Programme, the Pact on State-owned Enterprise (as interpreted by Jacek Kuroń). Finally, the author proposes a thesis that Polish privatisation is of an elitist character and large groups of society are excluded from participating in it.